Multiperiod design and planning of multiproduct batch plants with mixed-product campaigns - Corsano, Gabriela (2009)
This work presents a multiperiod optimization model for multiproduct batch plants operating during several time periods with different characteristics because of seasonal and market fluctuations. This model simultaneously considers decisions about the design, operation, scheduling, and planning of the plant and the corresponding tradeoffs among them. Thus, decomposition mechanisms, which have been frequently used in previous approaches, are avoided through a formulation that takes into account the main elements of these problems. Besides, decisions are affected by different context conditions arisen by the multiperiod effect. Through a mixed integer nonlinear program, different alternatives of mixed production campaign are considered, handled by means of a novel set of scheduling constraints. This approach is posed for a fermen- tors network with high detail level in the description of the unit operations in a plant that produces yeast and ethanol.